Konsep Laras Salendro R.M.A. Koeosoemadinata pada Angklung Pentatonis Ragam Laras - Ega Fausta (Universitas Gadjah Mada, 2020)
Pentatonic Angklung with variety of tunings (APRL) is one of the angklung innovation products which is created in 2017 through an experimental process by Endah Irawan et.al. Generally, it is an ansamble music consisting of several types of instruments made of bamboo. This ensemble is a recent innovation in the world of traditional Sundanese art because it has distinctive pattern / system of scales which combines several patterns of dissolution in Sundanese karawitan namely Salendro, Degung and Madenda, which are commonly found in different ensembles. This paper will present the concept of dissolution which is applied in pentatonic angklung with a variety of tunings (APRL) adapted from the concept of laras salendro by R.M.A. Koesoemadinata.